Zonulin, a regulator of epithelial and endothelial barrier functions, and its involvement in chronic inflammatory diseases - Sturgeon, Craig; Fasano, Alessio (Tissue barriers, 2016)
Beside digesting nutrients and absorbing solutes and electrolytes, the intestinal epithelium with its barrier function is in charge of a tightly controlled antigen trafficking from the intestinal lumen to the submucosa. This trafficking dictates the delicate balance between tolerance and immune response causing inflammation. Loss of barrier function secondary to upregulation of zonulin, the only known physiological modulator of intercellular tight junctions, leads to uncontrolled influx of dietary and microbial antigens. Additional insights on zonulin mechanism of action and the recent appreciation of the role that altered intestinal permeability can play in the development and progression of chronic inflammatory disorders has increased interest of both basic scientists and clinicians on the potential role of zonulin in the pathogenesis of these diseases. This review focuses on the recent research implicating zonulin as a master regulator of intestinal permeability linked to the development of several chronic inflammatory disorders.